Analisis Inflasi dan Jumlah Penduduk terhadap Pertumbuhan Ekonomi di Kota Kediri Tahun 2022 sampai Tahun 2024 - Nasrudin (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This theme is important to analyze because of the dynamics of the post-covid 19 economic sector in Kediri City. Using a quantitative approach, this study applies descriptive analysis to identify variable trends and correlation analysis to understand the associations between variables. The purpose of this analysis of inflation and population to determine: 1. The dynamics of inflation, population and economic growth in Kediri city in 2022-2024. 2. The effect of inflation on economic growth in Kediri city in 2022-2024. 3.The effect of population on economic growth in Kediri city in 2022-2024. Primary secondary data obtained from the Central Statistics Agency (BPS) Kediri. The main findings show a significant trend of disinflation in Kota Kediri from 2022 to 2024, accompanied by consistent population growth. Kediri's economic growth shows fluctuations, with a decline in 2023 followed by a recovery in 2024, while Gross Regional Domestic Product (GRDP) per capita continues to increase